의료보험 가입여부별 항생제 사용비교 - 박성옥 (연세대학교 보건대학원, 1988)
[한글] 의료보험 가입군과 비가입군간에 항생제사용의 비용과 사용량을 비교하기 위해 한 병원에서 1985년 1월1일부터 1987년 8월31일까지 퇴원한 기관지폐렴 소아환자 222명과 충수돌기절제술 환자 143명의 합 365명을 대상으로 의무기록지와 의료보험 수가 명세서를 이용하여 의료보험 비가입환자의 항생제사용을 보험수가로 환산한 후 보험가입구노가 비가입군가의 평균 항생제비용에 관하여 χ**2검정, ｔ검정으로 비교분석 하였다. 충수돌기절제술 환자에서는 항생제비용이 통계학적으로 유의한 차이가 없었다. 기관지폐렴 소아환자에서는 보험가입군의 항생제비가 비가입군에 비해 2배나 되어 통계학적으로 유의한 차이를 보였고, 그 종류도 의료보험 환자에서 고가인 Cephalosporin계 약물으 주로 사용하였다. 이와같이 의료보험 가입군의 항생제비용이 비가입군에 비해 높았고, 세균동정검사 실시여부별 의료보험 가입군과 비가입군과의 항생제비용 비교에서도 같은 결과였다. 본 연구는 한정된 질환만을 대상으로 의료보험 가입군과 비가입군 간의 항생제사용의 비용 및 총 사용량에 대한 것만을 비교한 제한점이 있다. 앞으로 재원기간중에 항생제 사용의 질과양에 대한 동시검토로 면밀히 평가될 수 있는 심층연구가 있어야 할 것이다. [영문] In order to compare the quantity and expense of the antibiotic use between the insured patients and non-insured patients, the researcher compared and analyzed the average expenses and dosages of antibiotics in reference to the insured patients and non-insured patients by means of the κ**2-test and t-test. The researcher treated with the total 365 patients; the 222 discharged bronchopneumonia infantile patients and the 143 appendectomy patients based on the medical record and the medical insurance payment details form the 1st of January in 1985 to the 31st of August in 1987. And in dealing with the antibiotic expense on the non-insured patients, they were converted to the medical insurance payment level. There are statistically no significant differences at the expense of the antibiotic use for the appendectomy patients, but some significant difference about twice as that of the antibiotic expense of the insured patients, compared with the non-insured patients for the bronchopneumonia infantile patients. And as to medicines, the insured patients are used the expensive Cephalosporin medicines. As the result of the above research, the expense of the antibiotic use for the insured patients was higher than that of the non-insured patients, and this was the same in case of the bacterial identified test. This study shows that there are some significant differences through the comparison in reference to the amount and expense of the antibiotic use in dealing with the limited diseases. It is necessary, hereafter, to work on a deep study to be able to precisely estimate the quantity and quality of the antibiotic use in hospital through a team work.
보건학과/석사